2012
DOI: 10.1542/peds.2011-2872
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Associated Necrotizing Enterocolitis: A Meta-analysis of Observational Data

Abstract: Recent exposure to transfusion was associated with NEC in neonates. Neonates who developed TANEC were at overall higher risk of NEC. TANEC patients were at higher risk of mortality, but additional studies adjusting for confounders are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
189
7
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(218 citation statements)
references
References 25 publications
7
189
7
15
Order By: Relevance
“…In a meta-analysis of 11 retrospective case-control studies and one cohort study, Mohamed and Shah reported the association between blood transfusion and NEC. 76 The total number of transfusionassociated NEC cases in the meta-analysis was 365. The OR of NEC being present after a recent blood transfusion was 2.01, indicating a significant association.…”
Section: Blood Transfusionmentioning
confidence: 99%
“…In a meta-analysis of 11 retrospective case-control studies and one cohort study, Mohamed and Shah reported the association between blood transfusion and NEC. 76 The total number of transfusionassociated NEC cases in the meta-analysis was 365. The OR of NEC being present after a recent blood transfusion was 2.01, indicating a significant association.…”
Section: Blood Transfusionmentioning
confidence: 99%
“…It may be argued that a restrictive transfusion practice is preferable, as more very preterm infants avoid transfusion without a worse outcome [26]. An alternate interpretation may be that a liberal transfusion practice is better for the possibility of a post hoc advantage in cognition [23].…”
Section: Current Rct-based Recommendationsmentioning
confidence: 99%
“…Several uniquely neonatal adverse associations have been demonstrated in epidemiological studies [29]. These include death [30], necrotising enterocolitis (NEC) [26,31], intraventricular haemorrhage (IVH) [32,33], retinopathy of prematurity (ROP) [34] and chronic lung disease (CLD) [35]. It is important to note however, that these observational studies using case control or retrospective cohort methodology report risk ratios for NEC following exposure to RBC transfusion that far exceed those demonstrated in randomised trials.…”
Section: Transfusion Safetymentioning
confidence: 99%
“…21 In addition, with new evidence from recent studies that demonstrate potential side effects of red cell transfusions, such as extension of ICH and transfusionassociated NEC, [11][12][13]22 the need to study the safety and efficacy of ESAs, in combination with restrictive transfusion guidelines, urgently increases. This is the first prospective, randomized, masked, multicenter study of early Darbe administered to preterm infants, and the first study of ESA administration to preterm infants that resulted in a significant decrease in both donor exposure and transfusion number.…”
Section: Figurementioning
confidence: 99%
“…In both analyses the importance of 1 or 2 fewer transfusions was questioned. 27,28 However, this benefit might have greater clinical significance in light of recent associations between early transfusions and severe ICH, 12 late transfusions and the development of NEC, 11,22 and potentially damaging concentrations of heavy metals, such as lead and mercury. 29 It is possible that even 1 to 2 fewer transfusions at key periods during a NICU course could be beneficial.…”
Section: Figurementioning
confidence: 99%